Phase synchronized 6 Hz transcranial electric and magnetic stimulation boosts frontal theta activity and enhances working memory - Tiam Hosseinian; Fatemeh Yavari; Min-Fang Kuo; Michael A. Nitsche; Asif Jamil (NeuroImage, 2021)
Network-level synchronization of theta oscillations in the cerebral cortex is linked to many vital cognitive functions across daily life, such as executive functions or regulation of arousal and consciousness. However, while neuroimaging has uncovered the ubiquitous functional relevance of theta rhythms in cognition, there remains a limited set of techniques for externally enhancing and stabilizing theta in the human brain non-invasively. Here, we developed and employed a new phase-synchronized low-intensity electric and magnetic stimulation technique to induce and stabilize narrowband 6-Hz theta oscillations in a group of healthy human adult participants, and then demonstrated how this technique also enhances cognitive processing by assaying working memory. Our findings demonstrate a technological advancement of brain stimulation methods, while also validating the causal link between theta activity and concurrent cognitive behavior, which may ultimately help to not only explain mechanisms, but offer perspectives for restoring deficient theta-band network activity observed in neuropsychiatric diseases.